2021
DOI: 10.1016/j.cmpb.2021.106402
|View full text |Cite
|
Sign up to set email alerts
|

A model based on cellular automata for investigating the impact of lockdown, migration and vaccination on COVID-19 dynamics

Abstract: B ackground and Objective COVID-19 pandemic continues unabated due to the rapid spread of new mutant strains of the virus. Decentralized cluster containment is an efficient approach to manage the pandemic in the long term, without straining the healthcare system and economy. In this study, the objective is to forecast the peak and duration of COVID-19 spread in a cluster under different conditions, using a probabilistic cellular automata configuration designed to include the observed char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
1
11
0
2
Order By: Relevance
“… 1997 ; Maniatty et al. 1999 ; Jithesh 2021 ; Gwizdalla 2020 ; Pereira et al. 2021 ; Bouaine and Rachik 2018 ; Blavatska and Holovatch 2021 ; Monteiro et al.…”
Section: Related Workunclassified
“… 1997 ; Maniatty et al. 1999 ; Jithesh 2021 ; Gwizdalla 2020 ; Pereira et al. 2021 ; Bouaine and Rachik 2018 ; Blavatska and Holovatch 2021 ; Monteiro et al.…”
Section: Related Workunclassified
“…Subsequently, Wolfram [39] proposed a simpler version of CA with two states per cell and three-neighbourhood. Research of a large number of authors from diverse disciplines has enriched the field of CA [40][41][42][43][44] and some researchers used CA to understand the dynamics of COVID-19 [45][46][47][48][49]. The book [44] covers a comprehensive survey of CA theory and wide varieties of applications.…”
Section: Cellular Automata (Ca) Preliminariesmentioning
confidence: 99%
“…There are 2 8 = 256 such rules for three-neighborhood CA. The decimal value derived out of 8 bit string of two CA rules (45) and (105) are illustrated in Table 1 Row 4 and 5. Eight different input combinations of a CA rule is a triplet of binary bits -111 (7), 110 (6), 101 (5), 100(4), 011(3), 010(2), 001 (1), 000(0), are noted on row 1 of Table 1.…”
Section: Cellular Automata (Ca) Preliminariesmentioning
confidence: 99%
“…The results showed that the global COVID-19 pandemic network has special complex network characteristics. Jithesh [ 15 ] used the cellular automata which initially configured to have only susceptible and exposed states. Enlarged and evolved in discrete time steps to different infection states of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%